The effect of Co on elastocaloric and mechanical properties of Ni-Co-Mn-Al alloys. (October 2019) - Xuan, Haicheng; Cao, Ting; Liu, Shilong; Wang, Libang; Xie, Zhigao; Liang, Xiaohong; Chen, Fenghua; Han, Peide
Abstract: The influence of Co substitution for Ni on the martensitic transformation, microstructure, mechanical properties and elastocaloric effect in Ni50-x Cox Mn32 Al18 (x = 5, 6 and 7) shape memory alloys has been investigated. The martensitic transformation temperatures can be tuned by controlling the Co content and shifts toward lower temperature region with the Co content increases in Ni50-x Cox Mn32 Al18 (x = 5, 6 and 7) alloys. Besides, the eCE performances and mechanical properties of these alloys can be effectively enhanced by alloying with Co. The maximum compressive strength about 1228 MPa is obtained in Ni43 Co7 Mn32 Al18 alloy. These alloys exhibit high sensitive to the strain rate and a large adiabatic temperature change of about 6 K is observed in Ni43 Co7 Mn32 Al18 alloy under the uniaxial stress of 600 Mpa. These results show that Ni50-x Cox Mn32 Al18 alloys would be the promising candidates for new multifunctional materials. Highlights: The effects of alloying with Co on mechanical properties and elastocaloric effect have been investigated. The martensitic transformation temperatures can be turned by controlling the Co content. The mechanical properties and elastocaloric effect can be effectively enhanced by alloying with Co. A high temperature change of 6 K is obtained at room temperature in Ni43 Co7 Mn32 Al18 alloy.